2016
DOI: 10.11648/j.ijmsa.20160502.16
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of Composite Brake Pad Using Pulverized Cocoa Beans Shells Filler

Abstract: Application of asbestos in friction material after a very long period is now discouraged due to its carcinogenic nature. There is need for alternative (human friendly) friction material. Hence the development of asbestos-free friction material from an agro-waste (cocoa beans shells-CBS) as filler element cum other additives was undertaken using powder metallurgy technique. The particulate size of the filler material considered was 300µm and epoxy resin was used as binder. The produced brake pad samples were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The outcome reveals that wear rate reduced with the growth in wt% of the resin. Olabisi et al [37] analysed the wear rate for the pulverized cocoa beans shell epoxy composite and obtained the wear rate of 3.934 mg/m. Yawas et al [38] studied the wear rate of periwinkle shell filled composite and concluded that the wear rate reduced as the corresponding powder size reduced.…”
Section: Brake Pads With Single-fillersmentioning
confidence: 99%
“…The outcome reveals that wear rate reduced with the growth in wt% of the resin. Olabisi et al [37] analysed the wear rate for the pulverized cocoa beans shell epoxy composite and obtained the wear rate of 3.934 mg/m. Yawas et al [38] studied the wear rate of periwinkle shell filled composite and concluded that the wear rate reduced as the corresponding powder size reduced.…”
Section: Brake Pads With Single-fillersmentioning
confidence: 99%
“…The wear rate of commercial conventional asbestos based brake pad is 3.8 x 10 -6 g/m (Olabisi et al, 2016) while the range of wear rate of all the composites obtained in this study is (1.909 -2.705) x 10 -6 g/m. This is much lower than that of asbestos based conventional brake pad and is an indication that the composites have the potential of better performance when used as brake pads.…”
Section: Weight Loss and Wear Rate Of The Compositesmentioning
confidence: 63%
“…The agro-waste based inoculant raw material (CBS) was obtained separately (Figure 1), well sun-dried, and cleaned to remove impurities. It was then crushed, and pulverized into a fine powder and sieved using different sieves of 150, 225, and 300microns aperture respectively [16]. The samples were sand cast in the foundry workshop.…”
Section: Method/experimental Proceduresmentioning
confidence: 99%